A Comprehensive Review of the On-Road Wireless Charging System for E-Mobility Applications - S, Yuvaraja; R, Narayanamoorthi; Sathik Mohamed Ali, Jagabar; Almakhles, Dhafer (Frontiers in Energy Research, 2022)
The recent progress in the dynamic wireless power transfer (DWPT) system brings feasibility to increase the driving range of an electric vehicle (EV). The on-road wireless charging system reduces the volume of the EV’s battery and charging the vehicle while driving. So, the powered roadways can potentially decrease the dependency on heavy-sized batteries for EV applications. The capability of transferring maximum power from the ground surface to the vehicle requires the critical design of the entire DWPT system. The various factors such as wireless charging pads, power electronic converters, compensators, and controllers influence the power transfer rate of the system. An appropriate impedance matching network assists the system during power transfer. Moreover, the design of coils in DWPT needs to consider the sensitive misalignment tolerance, safety issues, complex design, and cost factors. In this article, the basic topologies, history, and fundamentals of the DWPT charging system are discussed. In addition, the impact on the power grid due to the DWPT system and factors involved in microgrid integration are discussed. However, the current scenario of different compensators, converters, and design topologies proposed in the dynamic charging system is included. This article presents a comprehensive overview and challenges involved in a DWPT system such as the design of a power converter, charging couplers, compensation network, foreign object detection system, economic factors, and microgrid-integrated DWPT system. An economic analysis, electromagnetic compatibility, and interference of the charging system are also analyzed vastly. The human exposure level with its allowable limits developed for the wireless power transfer system is discussed.